Energizing Foreign Language Learner in English Reading Class through the Use of Word Webs Technique - Meiga Ratih Tirtanawati (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Reading is an activity with a purpose. Students may read in order to gain information or verify existing knowledge. They may also read for enjoyment or to analyze a writers‟ idea or writing style. One of important factors which contribute to the better reading comprehension is students‟ motivation in reading. Unfortunately, although reading is considered to be an important language skill, many students are not interested in reading because many teachers use monotonous reading activities. This paper focuses on analyzing the importance of using Word Web technique and highlighting the implementation the technique in teaching reading. Next the paper discusses the advantages and the classroom experience on the use of Word Webs Technique in teaching reading. The subjects are Second Semester of English Department Students. This study employed a qualitative research design and the data are collected through observation and questionnaire. Word webs technique have many positive advantages compared with another teaching technique. It is highly motivating, giving a sense of achievement in understanding further reading. Word Web technique makes the students use their prior knowledge and information to answer specific questions. With Word Webs Technique the process learning become more enjoyable and interesting. It is recommended for students to apply Word Webs Technique to get better reading ability.